Design of Real-Time Emergency Response System for Highway Networks: Application for High Frequency of Traffic Emergency Events During Peak Hours. Issue 1 (January 2015) - Kim, Woon; Kim, Hyeonmi; Chang, Gang-Len
This paper proposes a general framework of real-time emergency response operations for highway networks experiencing a high frequency of concurrent traffic emergency events. The proposed system consists of three principal models working collectively to optimize the location assignment of available response units, to estimate the probabilities of event occurrences, and to project the incident clearance time. This system was designed to assist responsible agencies in assessing the need to relocate available incident response units in real-time operations on the basis of the available resources and detected traffic information. Because the proposed system was designed mainly for the traffic incident management teams to respond to the traffic emergency events, it aimed to improve the networkwide traffic condition and the service performance by solving multiple conflicting objectives. This aim is different from most existing studies that target mainly emergency medical service. The empirical evaluation results using the incident data from I-695–MD-695 in Maryland showed that the dynamic real-time dispatch strategy could outperform the static dispatch and state-of-the-practice patrolling strategies with respect to minimizing the total delays induced by incidents. Furthermore, the dynamic dispatch strategy will enable the operating agency to use the available resources better than will the static dispatch strategy, especially when many traffic emergency events in congested corridors may occur in a relatively short time period.